2002
DOI: 10.1079/nrr200247
|View full text |Cite
|
Sign up to set email alerts
|

Comparative mammalian choline metabolism with emphasis on the high-yielding dairy cow

Abstract: The present review examines the importance of choline in dairy cow nutrition. Choline is an essential nutrient for mammals when excess methionine and folate are not available in the diet. The requirement for choline can be met by dietary choline and by transmethylation reactions. Two types of functions for choline are known: functions of choline per se; functions as a methyl donor. The two principal methyl donors in animal metabolism are betaine, a metabolite of choline, and S-adenosyl-methionine, a metabolite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
102
2
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(120 citation statements)
references
References 65 publications
8
102
2
8
Order By: Relevance
“…The exact mechanism by which vitamin E alone or in combination with choline can affect milk fat is not known. Although it is plausible that choline can have a positive effect on lipid trafficking and lipid transport to extra-hepatic tissues, including the mammary gland (see Pinotti et al, 2002 for references), effects of vitamin E on this situation are difficult to envisage and may merit further investigation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact mechanism by which vitamin E alone or in combination with choline can affect milk fat is not known. Although it is plausible that choline can have a positive effect on lipid trafficking and lipid transport to extra-hepatic tissues, including the mammary gland (see Pinotti et al, 2002 for references), effects of vitamin E on this situation are difficult to envisage and may merit further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…In dairy ruminants, the dietary availability of choline is still low, but the output of methylated compounds in milk is high, and precursors from the tetrahydrofolate pathway are often limiting, especially at the onset of lactation (Pinotti et al, 2002;Girard and Matte, 2004). Based on those considerations, the effects of rumen-protected choline (RPC) supplementation to transition cows have been investigated in several studies.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies (Piepenbrink and Overton, 2000;Pinotti et al, 2002;Cooke et al, 2007) suggested that high-producing cows may be choline deficient around parturition, which adversely affects liver functions, especially the synthesis and secretion of VLDL. Higher choline supply may increase milk production (Erdman and Sharma, 1991;Hartwell et al, 2000;Pinotti et al, 2003) but this response is strongly influenced by -E-mail: husveth@georgikon.hu other nutrients such as protein and methionine (Emmanuel and Kennelly, 1984;Hartwell et al, 2000;Brü semeister and Sü dekum, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the fact RPC can reduce non-esterified fatty acid concentration in plasma which contribute majority of fatty acids secreted by the mammary glands in dairy cows (Pinotti et al, 2002;Cooke et al, 2008). Change in Fat% can also be understood by the fact that it is negatively correlated with milk yield.…”
Section: Milk Production and Compositionmentioning
confidence: 99%